Negative Thermal Expansion Design Strategies in a Diverse Series of Metal–Organic Frameworks. (18th September 2019) - Burtch, Nicholas C.; Baxter, Samuel J.; Heinen, Jurn; Bird, Ashley; Schneemann, Andreas; Dubbeldam, David; Wilkinson, Angus P.
Abstract: Negative thermal expansion materials are of interest for an array of composite material applications whereby they can compensate for the behavior of a positive thermal expansion matrix. In this work, various design strategies for systematically tuning the coefficient of thermal expansion in a diverse series of metal–organic frameworks (MOFs) are demonstrated. By independently varying the metal, ligand, topology, and guest environment of representative MOFs, a range of negative and positive thermal expansion behaviors are experimentally achieved. Insights into the origin of these behaviors are obtained through an analysis of synchrotron‐radiation total scattering and diffraction experiments, as well as complementary molecular simulations. The implications of these findings on the prospects for MOFs as an emergent negative thermal expansion material class are also discussed. Abstract : Design strategies for tuning the coefficient of thermal expansion in an array metal–organic frameworks (MOFs) are demonstrated. A combined experimental and theoretical analysis elucidates the origin of these behaviors. The implications of these findings on the prospects for MOFs as an emergent negative thermal expansion material class are discussed.